Demography, Clinical Features and Outcome of Bacterial Keratitis Presenting in Tertiary Eye Care in Nepal - Leena Bajracharya; Asta Ram Bade; Reeta Gurung (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: Bacterial keratitis is an important cause of ocular morbidity in developing country like Nepal and this warrants a detail study of it including its outcome. Material and Methods: Data of demography, clinical features and risk factors of bacterial keratitis were segregated from our previous cross-sectional study of microbial keratitis and retrospective data of treatment and outcome were taken from electronic medical record. Results: Among 123 cases of bacterial keratitis, 111 had bacteria isolated in the culture whereas 12 had bacteria seen only in Gram stain. Average age of patients was 52.6 years; 65(52.8%) were female; 68.3% of total subjects were farmers. Patients had visited the tertiary hospital at an average of 12.9 days since onset of symptoms. Of culture isolates, 55 were Streptococcus pneumonia followed by Staphylococcus aureus (n=25) and Streptococcus viridians (n=14). Regarding clinical characteristics, 78(63.4%) cases had hypopyon; 24.3% (n=30) had infiltrate size of >¼ of corneal surface; 16(13.0%) were either perforated or impending to perforate at presentation. Trauma was the main risk factor in 35% (n=43), followed by topical steroid (19.5%, n=24) and dacryocystitis (16.2%, n=20). Patients were treated with combination of fortified cefazoline and amikacin or monotherapy with moxifloxacin or ofloxacin. Overall, 90(73.2%) responded to medical treatment, 19(15.4%) underwent therapeutic penetrating keratoplasty and 3(2.4%) needed evisceration. Smaller sized ulcers had better healing rates (81%) with statistical significance. Conclusion: Patients with bacterial ulcers present late in tertiary eye center causing increased morbidity and even loss of eyes. Awareness, protective measures from trauma and proper treatment has to be undertaken for controlling its occurrence and for better prognosis of the ulcers.